Recognizing vocational qualifications of refugees : examples from 'Prototyping Transfer' - Böse, Carolin [Verfasser]; Tursarinow, Dinara [Verfasser]; Wünsche, Tom [Verfasser] (My University, 2017)
"The Recognition Act which entered into force on 1 April 2012 aims to provide better employment opportunities in training occupations for people with foreign vocational qualifications. This option is also of interest for refugees, many of whom were unable to bring with them the relevant documents needed for the vocational qualification to be recognised, such as a diploma or employment reference. However, under certain circumstances, a recog-nition procedure may also be carried out without documents by means of skills analysis. The article examines this option which is enshrined in the Berufsqualifikationsfeststellungsgesetz (BQFG) [Professional Qualifications Assessment Act], and presents initial experiences of its implementation." (author's abtract ; BIBB-Doku)
Anerkennung beruflicher Qualifikationen von Flüchtlingen
Keywords: P 1.5 Migranten; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; Flüchtling; Auslandsqualifikation; Anerkennung